2016
DOI: 10.4103/2152-7806.175898
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous thrombosis of giant intracranial aneurysm and posterior cerebral artery followed by also spontaneous recanalization

Abstract: Background:Spontaneous complete thrombosis of a giant aneurysm and its parent artery is a rare event. Their spontaneous recanalization is even rarer, with few reports.Case Description:A 17-year-old male patient presenting blurred vision and headache, with a history of seizures, was referred to our service. After further investigation with cranial computed tomography, magnetic resonance imaging (MRI), and cerebral angiography (CAG), it was diagnosed a thrombosed aneurysm of the posterior cerebral artery (PCA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Focal arterial stenotic segments are often observed proximal or distal to the dissecting aneurysm, suggesting mural damage, as seen in some cases in this series. The impaired vessel wall and associated stenosis can induce spontaneous thrombosis [1, 16], but when treated, the treatment of these aneurysms must also target the mass effect [7].…”
Section: Discussionmentioning
confidence: 99%
“…Focal arterial stenotic segments are often observed proximal or distal to the dissecting aneurysm, suggesting mural damage, as seen in some cases in this series. The impaired vessel wall and associated stenosis can induce spontaneous thrombosis [1, 16], but when treated, the treatment of these aneurysms must also target the mass effect [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to take into account the course of thrombosed intracranial aneurysms in association with simultaneous ICA occlusion to construct an effective management plan. Aneurysmal thrombosis may not be the end of the story; with further aneurysmal growth, persistent mass effect, distal thrombo-embolism, and aneurysmal re-canalization being all potential occurrences even with fully thrombosed aneurysms, as long as the parent vessel is patent [ 9 , 10 , 22 , 24 , 25 ]. However, the co-existent thrombosis and hence non-patency of the parent vessel raises the question if recanalization of the thrombosed aneurysm can occur.…”
Section: Discussionmentioning
confidence: 99%
“…However, the co-existent thrombosis and hence non-patency of the parent vessel raises the question if recanalization of the thrombosed aneurysm can occur. Even though the chances are extremely narrow, it is possible and has been reported in a case of a thrombosed PCA aneurysm with parent vessel occlusion followed by recanalization of the aneurysmal neck and PCA several years later [ 10 ]. To date, of all the reported cases of thrombosed CCA aneurysms with ICA occlusion, no recanalization has been reported [ 11 - 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported rare cases of completely thrombosed aneurysms that presented with recanalization, reenlargement, and ischemic events. [10][11][12] Therefore, craniotomy or endovascular treatment should be considered along with a follow-up, and the resection performed in this case is considered reasonable.…”
Section: Discussionmentioning
confidence: 99%